2022
DOI: 10.3389/fpubh.2022.1005622
|View full text |Cite
|
Sign up to set email alerts
|

Real-life cohort experience after implementing HIV pre-exposure prophylaxis for one year in northwest Spain

Abstract: IntroductionPre-exposure prophylaxis (PrEP) has become a useful tool to reduce the transmission of human immunodeficiency virus (HIV) in key populations. In this article we assessed the effectiveness, safety, adherence, sexually transmitted infections (STIs) dynamics, and frequency of anal dysplasia among a real-life cohort of PrEP users in Northwest Spain.MethodsA retrospective cohort study was undertaken in the Alvaro-Cunqueiro Hospital, Vigo which included every individual who started daily emtricitabine/te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…A cohort study that evaluated 1-year real-life use of PrEP 18 has found strong effectiveness, safety and tolerability of these therapies. However, a necessary point to highlight is that the authors report a significant incidence of sexually transmitted diseases other than HIV/AIDS, 20 which should arouse the interest in developing comprehensive strategies. Currently, studies are being carried out with biological models, where specific therapies are being developed, such as a product for vaginal application, exclusively for women, which may be more accessible in certain cases.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study that evaluated 1-year real-life use of PrEP 18 has found strong effectiveness, safety and tolerability of these therapies. However, a necessary point to highlight is that the authors report a significant incidence of sexually transmitted diseases other than HIV/AIDS, 20 which should arouse the interest in developing comprehensive strategies. Currently, studies are being carried out with biological models, where specific therapies are being developed, such as a product for vaginal application, exclusively for women, which may be more accessible in certain cases.…”
Section: Discussionmentioning
confidence: 99%